Passion and athletic satisfaction in brazilian basketball college athletes (Research, Society and Development, 2020)
Passion and athletic satisfaction are variables of positive psychology studied in the sports context, related to performance, and investigated at the national and international levels. The objective of the study was to analyze the passion and athletic satisfaction in Brazilian college basketball athletes, seeking to compare the passion and satisfaction of the athletes according to the time of experience and performance and to correlate the variables passion and satisfaction. 60 athletes were subjects, with an average age of 22.06 (± 3.01 years) average experience of 10.13 (± 3.61 years), participants of the 2017 Brazilian University Games. The data were analyzed by Wilcoxon tests, Friedman, U of Mann Whitney and Spearman’s correlation coefficient (p